2009
DOI: 10.1089/mdr.2009.0913
|View full text |Cite
|
Sign up to set email alerts
|

Highly Variable Patterns of Antimicrobial Resistance in CommensalEscherichia coliIsolates from Pigs, Sympatric Rodents, and Flies

Abstract: Antimicrobial-resistant Escherichia coli strains from pigs, sympatric rodents, and flies from two large farms in the Czech Republic with different antibiotic exposure histories were characterized based on antimicrobial resistance genes, integrons, and macrorestriction DNA profiles. Isolates of E. coli were tested for susceptibility to 12 antimicrobial agents according to the standard disk diffusion method. In resistant isolates, polymerase chain reaction was used to detect antibiotic resistance genes, integras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 44 publications
4
31
0
2
Order By: Relevance
“…E. coli strains resistant to four and five antibiotics simultaneously were the most prevalent (27.3% and 28.4%, respectively) (Table 2). Values obtained in this work agree with other authors whose studies were performed with isolates from countries where the surveillance programs have not been settled and antibiotic use is not properly regulated (Literak et al, 2009;Marchant and Moreno, 2013). The most frequent multiresistance profiles observed were TET-ENR-AMX-FLOR-FOSF (22.7%), TET-TIA-ENR (13.6%) and TET-ENR-AMX-FLOR (12.5%) ( Table 2).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…E. coli strains resistant to four and five antibiotics simultaneously were the most prevalent (27.3% and 28.4%, respectively) (Table 2). Values obtained in this work agree with other authors whose studies were performed with isolates from countries where the surveillance programs have not been settled and antibiotic use is not properly regulated (Literak et al, 2009;Marchant and Moreno, 2013). The most frequent multiresistance profiles observed were TET-ENR-AMX-FLOR-FOSF (22.7%), TET-TIA-ENR (13.6%) and TET-ENR-AMX-FLOR (12.5%) ( Table 2).…”
supporting
confidence: 90%
“…These results are in agreement with Literak et al (2009) (Lanz et al, 2003;Phongpaichit et al, 2007) and a high prevalence of E. coli carried class 1 integrons (Phongpaichit et al, 2007).…”
supporting
confidence: 89%
“…Humans may become infected with AMR bacteria through occupational exposure and ingestion of contaminated food and water (11). In addition, antimicrobials used on farms have been reported to increase AMR in organisms isolated from areas exposed to farm waste (12), as well as in the flora of wildlife trapped in their proximity (13,14).…”
mentioning
confidence: 99%
“…Moreover, many studies have found similarities in the patterns of resistance in bacterial isolates from livestock and small fauna, e.g., rodents (7,8), insects (7,9), or birds (9), from the farm settings. Thus, we were interested in determining whether wild ungulates in close contact with free-ranging livestock carry indicator bacteria with similar resistance profiles.…”
mentioning
confidence: 99%